Pendidikan Responsive Gender Usia 5-6 Tahun Melalui Permainan Fisik Untuk Anak Usia Dini - Nofianti, Rita; Nurhalimah Tambunan; Purwanti, Anggun Febri (Universitas Muhammadiyah Metro, 2025)
The problem in this study is the gap in the number of children between boys and girls which causes gender discrimination in every learning process in the classroom. Thus, it causes low interest in learning in children and can affect children's learning activities during school. The purpose of this study was to be able to analyze children's interests through physical games that differentiate between girls and boys. So that children do not discriminate between genders in playing and learning. The research method used a descriptive qualitative approach. The research subjects consisted of 30 children aged 5-6 years (15 boys and 15 girls), 3 early childhood education teachers, and 2 principals in two kindergartens. The research instruments included structured observation guidelines, semi-structured interview guidelines, field note sheets, and visual documentation. Data collection techniques used participatory observation, in-depth interviews, and documentation carried out for 3 months. Data analysis used the thematic analysis model of Braun and Clarke (2006) with the stages of data familiarization, initial coding, theme search, theme review, theme definition, and report preparation. With this method, researchers will obtain complete information about gender-responsive education. The results of the study show that the implementation of physical games designed with gender responsive principles can increase by providing equal opportunities for boys and girls to develop gross motor skills, self-confidence, and social skills without being limited by gender stereotypes. The implementation of physical games has been proven to increase gross motor development by 90% in girls and 85% in boys in the aspect of balance, increase children's confidence and self-efficacy in exploring physical activities without gender limitations, develop social skills and the ability to cooperate in heterogeneous groups, and help break down gender stereotypes through the understanding that abilities are not determined by gender but by individual effort and interest.